Morbidity in Dengue Patient with History of COVID-19 Infection: A Study from Tertiary Care Hospital in North India - Deval Brajesh Dubey; Swati Agnihotri; Shilpa Ulhas Vahikar; Shaila Kumari Mitra; Kanchan Srivastava; Amresh Kumar Singh; Ravikant Verma (Disease and Health Research: New Insights Vol. 4, 2024)
Background: The coronavirus disease (COVID-19) posed one of the deadliest pandemics since the outbreak of the Spanish flu. The already COVID-19 pandemic burdened nations, during epidemics have to cope up with dengue fever too. The continuous circulation of both viruses presented a significant problem for the healthcare system, which struggles with patient triage and prognosis. It’s suggested that dengue antibodies cross react with SARS-CoV-2. The coincident incidence of COVID-19 and dengue makes timely patient diagnosis, treatment and disease prevention difficult. However, it’s unknown whether patients with previous COVID 19 infection can develop immunity dengue virus. Aim: To study the hematological parameters in patients with active dengue infection and its correlation with past history of COVID 19 infection. Secondary aim: To investigate the effect of previous COVID-19 infection on various hematological parameters in patients with active dengue infection. To investigate previous Covid-19 infection. Effect of 19 infections on morbidity in patients with active dengue infection, evaluation of days of hospital stay, platelet transfusions, etc. Methods: A total of 189 patients were included in our study. The mean age was comparable between the two groups. Group A patients had a higher mean platelet count [0.68200.00 ± 0.28153.33 x106/cumm] than Group B patients [0.54181.21 ± 0.31792.06 x106/cumm]. Group A had substantially shorter hospital stays, averaging 0.380.83 days versus 3.213.24 days for Group B. In addition, Group A received a substantial reduction in platelet transfusions. Results. Patients with a previous history of COVID 19 infection had significantly lower circulating lymphocyte and monocyte counts, with lymphocytopenia previously described in patients coinfected with SARS CoV-2. However, patients with no history of previous covid-19 infection had substantially lower levels of monocytes and lymphocytes compared to those without a history. Conclusion: Our research indicates that patients with a prior history of COVID-19 infection have reduced dengue mortality. Patients with previous COVID-19 infections had higher platelet counts, shorter hospital stays, and fewer platelet transfusions than patients with no history of COVID 19 infection.